Prediction of Office Stationery Needs Using Polynomial Regression Method - Husni Johan, Arsyelina; Waluyo, Edy (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to determine the predicted demand for office stationery (ATK) for the upcoming year. The availability of sufficient and appropriate ATK reflects good governance within an organization. To achieve this, accurate and data-driven predictions of ATK needs are essential in the budget planning process. In this study, the method used to predict ATK demand is Second-Order Polynomial Regression. The accuracy of this method is assessed using the Mean Absolute Percentage Error (MAPE). The lower the MAPE value, the better the prediction accuracy. The results of the study indicate that the Polynomial Regression method provides reasonably accurate predictions, with an average MAPE of 22.41%.